Object oriented programming and applications of boundary element method in ground vehicle aerodynamics - Chiu, Tak Wai (Computer Assisted Methods in Engineering and Science, 2023)
The phenomenal development and popularisation of Object Oriented Programming (OOP) in recent years has created a new dimension in the innovation and implementation of powerful panel method techniques. Although many scientists and engineers are already employing OOP languages such as C++, some of them are still using the languages in a procedural and non-hierarchical manner, leaving a large proportion of these languages' capability unexplored. This paper presents the idea and implementation of OOP in the panel method, which is widely used in ground vehicle aerodynamics. Program examples will show that OOP enables the writing of highly modularised, reusable, readable and debuggable panel method programs.